PENGEMBANGAN MEDIA VIRTUAL CLASS MELALUI SMARTPHONE PADA DIKLAT TEKNIS PKB DI PERWAKILAN BKKBN PROVINSI BENGKULU TAHUN 2018 - Kesuma, Aria; Slamet, Adeng; Rachman, Fuad Abdur (Jurnal Inovasi Pendidikan, 2019)
This research purpose to produce media that are valid, practical and effective in learning education and training activities organized by the Field of Training and Development at the BKKBN Representative of Bengkulu Province. The method of this research is development research using the Alessi and Trollip development model which consists of three stages, namely the planning, design and development stages. The validation that has been done in study includes three things they are validation for media, validation for Material and Validation for learning design. From the results of the validation that has been done by the validators gets some suggestions and inputs in the form of developed media were declared valid and feasible to be tested. The value of practicality is good value which is the media that has been developed is very practical value from the perspective of participants. On the assessment of effectiveness obtained by Ngain is of 0.73 in the high category. From the results of this research can be concluded that the media that has been developed is valid, practical, and effective for the learning or technical training that held and suggested to other researchers to be able to develop this media and research in other related sectors.